A Discourse Analysis Of The Girls In Their Summer Dresses' Short Story By Irwin Shaw - Astuti, Febri; , Drs. M. Laila. M. Hum; , Drs. Dwi Harjanti. M. Hum (2013)
This research paper is aimed at identifying and explaining the seven criteria of textuality which make a short story of "The Girl in Their Summer Dresses" is a discourse. According to the background, this research is conducted to answer the research problems statement, what types and meaning of element of textuality found in the short story by Irwin Shaw are. The research is descriptive qualitative research. In collecting data, the writer employs documentation with classifying the data based on seven criteria of textuality. The writer analyzes the discourse in the short story using the data short story itself as primary and secondary data. The results of this study show that all the types of cohesion used in the short story "The Girls in Their Summer Dresses" are anaphoric reference and cataphoric reference refer to the meaning often appear "Michael and Frances". Then nominal substitution refers to the object "same", "one", and "any", verbal substitution refers to the object "do", and clausal substitution refers to the object "not". In nominal ellipsis refers to the meaning "the story", "me", "brandies", and "you", verbal ellipsis refers to the meaning "France or Michael said", "touched", and "speaking", clausal ellipsis refers to the meaning "I look at woman" and "the Stevenson that stop us". Besides, additive conjunction refers to the object of "and", clausal conjunction refers to the object "because" and "so that", temporal conjunction refers to the object "after", "next", "then", "later", "first" and "toward", adversative conjunction refers to the object "but", "anyway", and "even though". The lexical cohesion is consist of repetition refers to the object often appear "I", "and", and "you". Synonym refers to the object "a planned and a programmed", hyponym refers to the object "the girls in the office" and "pretty", metonymy refers to the object "a kid", "seven blocks", antonym refers to the object "woman and man", and collocation refers to the meaning "the term of woman in Fifth Avenue". Thus, another six criteria of textuality: coherence, intentionality, informativity, acceptability, situationality, and inter textuality are use to make The Girls in Their Summer Dresses' short story is as a discourse.